Schooling experiences of orphaned boys in one rural school in the Kingdom of Eswatini - Masuku, Mzikayifani Bizzah; Motsa, Ncamsile Daphne; Morojele, Pholoho (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The present study draws on the gender schema theory to explore the schooling experiences of three orphaned boys aged between 17 and 20. These boys were purposively sampled from grade 10 and 11 in a rural school in Eswatini. The study aims to provide insights into how their schooling experiences can be improved to empower them to challenge and overcome discriminatory gender norms prevalent in the Kingdom of Eswatini. The study employed a qualitative narrative method that included semi-structured individual and focus group interviews and photo voice to gather data. The findings of the study revealed that the education of orphaned boys was significantly impacted by the wrong stereotypes attached to the male gender label, which assumes that boys are solid enough to resist any difficulty. The study also found that various factors, such as cruel teachers, students, family members, society, and the boys themselves, acted as impediments to their education. The implications of these findings are discussed, and recommendations for future research are provided. The study concludes that traditional Eswatini societal norms and values impact the education of orphaned boys, as they are often stereotyped as strong and resilient individuals who can overcome any obstacle. To ensure that orphaned boys have a positive experience in school, the study recommends collaborative efforts from the government, schools, families, and communities to change their focus and support these children.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 8, 2024
Keywords: Boys; Eswatini; Orphanhood; Rural; Schooling Experiences; Rural schools; Rural schools -- Kingdom of Eswatini; Orphans; Education -- Kingdom Eswatini